2020
DOI: 10.1039/c9cc08700a
|View full text |Cite
|
Sign up to set email alerts
|

How to achieve a highly selective yet simply available vanadium phosphorus oxide-based catalyst for sustainable acrylic acid production via acetic acid-formaldehyde condensation

Abstract: A series of unsupported and supported vanadium phosphorus oxide catalysts were prepared by employing a new strategy, which significantly reduced the complexity of catalyst preparation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Therefore, it could be a good candidate as a dispersant. Our recent study confirmed that the SiO 2 materials of different porosity displayed significant impact on the overall performance of the dispersed VPO entities for the target reaction. Al 2 O 3 possesses certain acidity and large surface area, it can be used as dopant/dispersant.…”
Section: Resultssupporting
confidence: 74%
“…Therefore, it could be a good candidate as a dispersant. Our recent study confirmed that the SiO 2 materials of different porosity displayed significant impact on the overall performance of the dispersed VPO entities for the target reaction. Al 2 O 3 possesses certain acidity and large surface area, it can be used as dopant/dispersant.…”
Section: Resultssupporting
confidence: 74%
“…On a δ‐VOPO 4 /γ‐VOPO 4 (w/w, 3/1) catalyst at 360 °C, the total yield of acrylic acid and methyl acrylate reached 84.2% at the formation rate of acrylic acid and methyl acrylate of 1.71 mmol g −1 h −1 13 . The δ‐VOPO 4 , γ‐VOPO 4 , β‐VOPO 4 and (VO) 2 P 2 O 7 components are taken as the active phases 10,12,13 …”
Section: Introductionmentioning
confidence: 99%
“…In addition to the alkali-based catalyst, vanadium-phosphorusoxide (V-P-O) also has an appreciably catalytic activity in the aldol condensation reaction. 3,[10][11][12][13] When V-P-O oxides catalyzed the aldol condensation reaction between acetic acid and formaldehyde with an acetic acid/formaldehyde molar ratio of 2.5:1 at 340 °C in a fixed-bed reactor, the total formation rate of both methyl acrylate and acrylic acid reached 11 μmol g cat −1 min −1 at the formaldehyde conversion of 60%. 10 On a ⊐-VOPO 4 /γ-VOPO 4 (w/w, 3/1) catalyst at 360 °C, the total yield of acrylic acid and methyl acrylate reached 84.2% at the formation rate of acrylic acid and methyl acrylate of 1.71 mmol g −1 h −1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acquiring a highly efficient and stable catalyst is the key to realizing this technique. Therefore, many different kinds of catalysts were tested by researchers, such as vanadium phosphorus oxides (VPO), zeolites, , Cs/SiO 2 , and alumina supported alkali or alkaline earth metals oxides. Among them, alumina base catalysts exhibit excellent catalytic performance in aldol condensation due to their desirable textural properties and Lewis acid sites. Davis et al earlier prepared a series of cesium-based supported catalysts and applied them to the reaction of propionic acid and formaldehyde .…”
Section: Introductionmentioning
confidence: 99%